2019
DOI: 10.1007/s40858-019-00290-3
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fertilization effects on wheat blast epidemics under varying field environmental conditions

Abstract: Wheat blast, caused by the fungus Magnaporthe oryzae Triticum (MoT) pathotype, is one of the most important yield-reducing diseases of wheat, mainly in the tropical wheat-growing regions of South America. In this study, we assessed the effects of nitrogen (N) fertilization on wheat blast epidemics. Factorial experiments were carried out in Londrina (2015 and 2016) and Floresta (two sowings in 2017) with N rates (0, 40, 80 and 120 kg/ha for the first experiment, and 0, 60 and 120 kg/ha for the second) and wheat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…Thus, climate variability might override the depression effect of the low-external-input farming system on rice diseases. Other study found a positive association between the severity of wheat blast (caused by fungus M. oryzae ) and the amount of nitrogen fertilization in Brazil 40 .…”
Section: Discussionmentioning
confidence: 92%
“…Thus, climate variability might override the depression effect of the low-external-input farming system on rice diseases. Other study found a positive association between the severity of wheat blast (caused by fungus M. oryzae ) and the amount of nitrogen fertilization in Brazil 40 .…”
Section: Discussionmentioning
confidence: 92%
“…Metabolicamente, a forma amoniacal aumenta o teor de açúcar apoplástico e aminoácidos, bem como GABA (ácido gama-aminobutírico), aumentando assim a disponibilidade de nutrientes para o patógeno invasor (GUPTA et al, 2017). Já o nitrato, aumenta a produção de poliaminas (espermina e espermidina), que são sinais de defesa estabelecidos (SILVA et al, 2019).…”
Section: Nitrogêniounclassified
“…A balanced plant nutrition is required to avoid excess of certain amino acids in plant cells, which is used by the pathogen. The effect of nitrogen on wheat blast is not entirely clear, but studies suggested a positive association between nitrogen rate and wheat blast intensity (Huber and Thompson 2007;Silva et al 2019). The pathogen seems to be able to manipulate the plant system to obtain the required nutrients, thus causing physiological changes.…”
Section: Wheat Blast Managementmentioning
confidence: 99%